Mapping the Geographic Inequalities in Psychiatrist Distribution across Madhya Pradesh, India: An Exploratory Study - Roshan Sutar; Abhijit Pakhare; Anuja Lahiri; Yogesh Sabde; Vijender Singh (Indian Journal of Psychological Medicine)
Background: The National Mental Health Survey identified a vast treatment gap across India. This treatment gap is partly attributed to the availability and accessibility of mental health services in different states. Accessibility to a psychiatrist in Madhya Pradesh (MP) is essential due to the significant disparity among urban, rural, and tribal regions across the state. The study attempted to identify the geographical disparity of psychiatrists in MP to improve future mental health service delivery. Methods: An online survey of practicing psychiatrists was conducted in December 2022 in the settings of public and private healthcare service delivery systems through offline and online accessibility/availability of psychiatrists practicing in MP, and the data were mapped using geo-locations of psychiatrists and were analyzed using ArcMap 10.8.1. Results: In total, 152 psychiatrists were practicing in MP across 195 locations, which amounts to 0.21 psychiatrists per 100,000 population with a concentration around big cities. Out of 54 districts, 24 districts did not have any practicing psychiatrists. A total of 155 health facilities were identified across 30 (55.6%) districts where at least one psychiatrist provided mental health services. The nearest-neighbor index for 152 points was –13.69. Conclusions: Combining psychiatrist geo-mapping data with population data comprehensively explains the MP state’s mental health service delivery needs. It could be wise to improve the spatial distribution of psychiatrists in each district rather than achieving the recommended ratio of doctors to patients per state. These data need to be supplemented with qualitative inquiry to help policymakers and health planners generate effective public–private partnerships in mental health service delivery in the coming time.